Abnormal location of umbilical venous catheter due to Scimitar syndrome - Christopher R Mart; Charlotte S Van Dorn (Wolters Kluwer Medknow Publications, 2014)
Scimitar syndrome is a rare congenital anomaly where the right pulmonary veins return to the inferior vena cava (IVC) just below the diaphragm. On chest X-ray (CXR), an IVC catheter will be in a bizarre location outside the heart if it inadvertently passes into the scimitar vein rather than into the right atrium.